A survey on work-related musculoskeletal disorders among construction trades - Ahmad Nazri, Mohamad Izzat Al Ridhwan; Abas, Nor Haslinda; Mohd Affandi, Haryanti; Deraman, Rafikullah; Hasmori, Muhammad Fikri; Nagapan, Sasitharan; Abas, Nor Ain; Mustaffa Kamal, Mohd Firdaus (Penerbit UTHM, 2018)
Work-related musculoskeletal disorders (WMSDs) are the common health problem among workers in a construction site. Construction workers tend to experience neck pain, lower back pain, knee pain, leg fatigue and feet discomfort due to the occupation they performed. This study aims to investigate the issue related to musculoskeletal disorders among construction workers while performing construction works. Field observation was conducted at four construction sites in Perak Tengah district in order to identify the types of trades who exposed to musculoskeletal disorders. Next, a survey form was developed by modifying the existing Nordic Musculoskeletal Questionnaire (NMQ) in determining the symptoms of WMSDs. Surveys were carried out on 100 construction workers at the selected four construction sites to identify the area and causes of pain and discomfort, types of treatment received by the workers and recovery duration for pain and discomfort. Based on the survey, shoulder, wrists/hands and low back were the common area of pain or discomfort after and while performing works. The main causes of pain and discomfort were mostly from repetitive works, awkward working postures and manipulation of heavy load. Types of treatment received by workers were taking a medicine and rest, while the recovery duration for pain or discomfort was around a week. Interviews with panels of expert regarding the strategies or best practice to minimize the WMSDs among construction workers revealed that the most preferable practice is the contractor of the construction project should follow the safety and health regulation, particularly in managing WMSDs, such as implementing medical surveillance for workers. This study will help construction stakeholders, especially contractors to discover the type of occupations that are majorly impacted with WMSDs and further provide the best strategies or control measures to reduce the effect of WMSDs to their employees while performing work